Batch isolation of novel sequences targeting regions of rapid viral variations - Yu, Wenwen; Yang, Xinmin; Gao, Ye; Zhang, Xiaoxia O; He, Ran; Ma, Xiaoqian; LV, Miao; Cui, Rongfeng; Feng, Shulil; Kao, Yongchang; Xie, Shaoping; Shi, Wei; et al. (The Indian Journal of Animal Sciences, 2012)
Rapid evolution is widespread in the viral kingdom and a major concern for developing universal vaccines. The isolation of large numbers of viral sequence variants at highly variable regions in viral proteins remains a daunting challenge. Foot-and-mouth disease virus (FMDV) is a picornavirus and an underlying cause of a highly contagious disease of cloven-hoofed animals which often results in substantial economic losses. This study aimed at developing a combined method for the isolation of novel sequences to cope with rapid viral variations at the G-H loop of FMDV VP1 protein. DNA primer sets harbouring random nucleotides scattered in the G-H loop region, carrying additionally coding sequences for a T cell epitope and the carboxyl terminus, were designed and assembled by asymmetric PCR. After eliminating insert-free vector background and enriching positive clones, 100 novel sequences targeting the rapid viral variations of the G-H loop were obtained from 2 plasmid libraries. The method allowed radical changes in amino acid sequence, and our study has identified critical steps in the batch discovery of viral sequence variants, paving the way for future research on the possibility of developing a polyvalent universal vaccine.